Characterization of the phytochemical profile of the flowers of Turnera ulmifolia L. (Chanana) (Research, Society and Development, 2020)
Chanana (Turnera ulmifolia L.) is a herbaceous plant, native from tropical America, Africa, India and Southeast Asia, with wide geographical distribution in the regions of northeastern Brazil. The plant is widely used by folk medicine, and its flowers are used to treat skin lesions and inflammatory processes. In view of the scarcity of studies related to the phytochemical composition of its flowers, this experimental study aimed to analyze the phytochemical profile of T. ulmifolia flowers, using qualitative methods of phytochemical detection. The study was developed through the analysis of two extracts, one aqueous (EAFC) and the other hexane (EHFC), applying maceration as an extraction method. The results showed that chanana flowers have a variety of secondary metabolites, such as alkaloids, steroids, triterpenoids, anthocyanidins, chalcones, coumarins, flavonoids and tannins. Among the extracts analyzed, EAFC was shown to be richer in phytochemicals compared to EHFC. The study showed that flowers are rich in relevant secondary metabolites, which can be directly related to their medicinal properties described by popular uses. In addition, this research showed the presence of compounds not yet detected in studies related to the chemical composition of the species, such as triterpenes, anthocyanidins and chalcones.